Level of acceptability of Philippine Cuisine with a twist in selected restaurants: Mesa Filipino Moderne and Simple Lang - Ma. Teresa Cunanan, Jherus de Jesus, Dara Fenella Gabriel, Roselyn Ruiz, and Tereseita Sebastian. 4 0 16; 5
u
Undergraduate Thesis: (B.S. of Hotel and Hospitality Management) - Pamantasan ng Lungsod ng Maynila, 2015.
Keywords: 2 -- 0; 6; 20; 20; 2